Uveitis at the juvenile ankylosing spondylitis and in cases of onset disease in the adult age - O.E. Chernyshova; A.K. Pavliuchenko; T.R. Polesova; O.V. Syniachenko; M.F. Giulmamedova (Zaslavsky O.Yu., 2017)
Background. The prevalence of ankylosing spondylitis (AS) among the population reaches 0.3 %, which is much more likely to develop at the age of 20-30 years. Two forms of AS are distinguished: pediatric and adult, depending on the age of the disease debut. The diagnosis of juvenile AS (JAS) is one of the most urgent problems in pediatric rheumatology. Regardless of the patients' age, the choroid inflammation is an often serious systemic manifestation of AS. At the same time, the evolution of JAS in adulthood remains unexplored. The purpose of research was to study patients with AS regarding the incidence and nature of uveitis course and to evaluate disease characteristics while its onset in childhood and adulthood. Materials and methods. Two-hundred and seventeen patients with AS (193 men and 24 women) with an average age of 38 years were examined. The fast-progressing course of a disease was detected in 21 % cases, moderate and high degree of activity in 79 % cases, ІІ-ІІІ stage in 82 %, and polyarthritis in 65 %. JAS was detected in 16 % cases (all boys), among them the third stage occurred twice as often among the other patients. Results. Choroid inflammation within JAS formation develops in 42 % cases, and among patients with the disease debut in adulthood - 4.6 times less often, in addition, in the 1st group the peripheral, anterior, total and posterior uveitis correlates as 7 : 5 : 2 : 1, it has a one-sided character, 4 times more often characterized by acute course, whereas in the 2nd group the anterior variant of this ophthalmopathy is typical, in the every second case there was the bilateral intermittent uveitis, and regardless of age at the disease onset it is closely related with high AS activity. In patients with JAS there is a correlation with gonarthritis and encephalopathy, in other cases with the integral index of arthritis activity, the coxitis presence and spondylopathy prevalence. In its turn, in the observations of the AS in 1st and 2nd groups the multidirectional connections the pathogenetic architectonics of ophthalmopathy with serum C-reactive protein concentration were determined, and therefore high rates of immunoglobulin G and tumor necrotic factor α are risk factors. Conclusions. The AS onset in childhood is a risk factor for the severe course of such ophthalmopathy as uveitis.